Israel : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The paper suggests that several factors, besides tight monetary policy, may well have contributed to the high real interest rates that have been observed in Israel. The paper examines the impact of unanticipated changes in nominal interest rate monetary policy shocks on a number of variables in Israel. The paper provides evidence that the inflation expectation measure derived from the capital markets tends to overstate the trend in actual inflation. The paper also provides statistical data on the economic indices of Israel.